Using Religious Character Education to Help Students Develop Exceptional and Moral Character - Zaenol Fajri; Luluk Kamilah (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study's backdrop stems from the growing emphasis on religious character in recent years. This study aims to explain how Islamic character education is used at Madrasah Tsanawiyah Nurul Jadid to help students develop outstanding and honest characters. Methodology: Interviews, observations, and documentation were used to gather data for a case study approach using a qualitative method. Main Findings: The study's findings show that incorporating Islamic values into the curriculum, establishing religious practices like congregational prayer, tadarus Al-Qur'an, and daily prayers, and having teachers set an example regarding their attitudes and behavior are all ways to implement religious character education. A structured educational system, teacher collaboration, a positive school climate, and sufficient infrastructure support this implementation's success. In the meantime, challenges include a lack of parental support, scheduling constraints, and various student backgrounds. Novelty/Originality of this study: The study concludes that while religious character education helps students develop high, disciplined, and responsible morals, it still needs close collaboration between families and schools to produce the best results.